Šport na Filozofski fakulteti - Ravbar, Ana (Šport (Ljubljana), 2019)
Sport has been part of the Faculty of Arts since the sixties. The breakthrough was the employment of sports educators. Since then, sports activities and the number of students involved in them have been increasing. Sports at the Faculty of Arts plays a health, especially a recreational and competitive role. Since the female population is dominated, sports offer is very diverse and is largely adapted to female students. Today, physical education is part of a ECTS credit rating of the elective subject of Physical Education and Humanities. It consists of theoretical subjects and practical sports programs. Currently, five physical education teachers are employed at the Physical Education division. Students regularly and successfully represent the colors of Faculty of Arts at sports competitions, both at the national university level as well as at the international level.
Keywords: Faculty of arts; Filozofska fakulteta; physical education; sport; students; šport; športna vzgoja; študenti; University of Ljubljana; Univerza v Ljubljani